Sustainability Chinese style: The concept of the "harmonious society" - Gudrun Wacker; Matthis Kaiser (Stiftung Wissenschaft und Politik (SWP), 2008)
On the basis of its economic and political importance, China is seen as a great power and upcoming superpower, and Beijing plans to quadruple GDP again between 2000 and 2020. But despite the "reform miracle," China's pro-capita GDP is still below the global average and the country is facing enormous domestic challenges. The price of more than three decades of rapid economic growth is high: wasteful use of energy, massive pollution, a threefold income gap (between rich and poor, city and countryside, and coastal and inland regions), and a threadbare social safety net. On top of that, there is corruption at all levels and a lack of good governance. These enormous domestic problems endanger China's stability and have international repercussions too, for example in the form of transfrontier pollution and climate change.In order to counteract these negative trends the Communist Party leadership in-troduced two new principles in 2003/2004-namely, "scientific development" and the "harmonious society"-in order to bolster its legitimacy and enhance its stand-ing in society. Specifically it is attempting to remedy the identified problems and at the same time offer a substitute for an ideological superstructure that has lost much of its relevance. This study focuses on the issues of environment/energy and social inequality/welfare and investigates what measures have been planned and enacted under the "harmonious society" policy, the impact they have actually had, and where their limits lie
Keywords: 320; Volksrepublik China; Einkommensverteilung